Structural properties and defect related luminescence of Yb-doped NiO sol-gel thin films. (February 2020) - Zargouni, S.; El Whibi, S.; Tessarolo, E.; Rigon, M.; Martucci, A.; Ezzaouia, H.
Abstract: In this work, ytterbium doped nickel oxide thin films were successfully synthesized and deposited on glass substrates using the sol-gel method combined with the spin-coating technique. The structural, morphological and optical properties of the films were investigated through XRD, AFM, UV–Vis and PL spectroscopy. Doping NiO with low Yb 3+ ions content (1%, 2% and 3%) highly affected the lattice periodicity of the cubic nickel oxide structure through possible substitution of Ni atoms by higher sized Yb atoms, increasing the unit cell volume of the films and causing additional strains in the host lattice. The average crystallite size of the films varies between 4.34 nm and 8.25 nm. Morphological studies indicate a significant decrease in the surface roughness of the films from 2.5 nm to 0.4 nm with increasing Yb content. The as synthesized thin films are relatively transparent especially in the IR region. Room temperature PL spectra confirmed the presence of point defects such as nickel vacancies ( V N i ) and oxygen interstitials ( O i ). The effect of trivalent Yb 3+ ions doping was investigated using Gaussian distribution. The variation of the position and intensity of sub-gap luminescence centers suggests the formation of secondary phases inside of NiO lattices contributing to the quenching of luminescence.